Efficiently removing phenols from aqueous solution using amino acid functionalized D301 resins. Issue 15 (13th October 2019) - An, Fu-Qiang; Li, Hu-Fei; Guo, Xu-Dong; Xue, Xiao-Yan; Wang, Yong; Hu, Tuo-Ping; Gao, Jian-Feng
ABSTRACT: Amino acid functionalized D301 resins (Tyr-D301, Phe-D301, and Ala-D301) are successfully prepared to remove phenols. The influences of adsorption condition on adsorption ability and the practical application value are investigated. The functionalized D301 resins possess strong adsorption ability toward phenol by ways of hydrogen bond interaction. The adsorption capacity of Tyr-D301, Phe-D301, and Ala-D301 is 388.2, 368.4, and 321.5 mg· g −1 at 293 K and pH of 2, respectively. The adsorption process could be described satisfactorily by Lagergren-first-order model and Langmuir model. The rate constant is 0.057, 0.042, and 0.035 min −1, respectively. The functionalized D301 can be used to dispose wastewater containing phenols.